POLA KOMUNIKASI DALAM KRISIS PERNIKAHAN PADA PRAMUGARI MASKAPAI INTERNASIONAL - Julia Ratnasari Dewi (Universitas Prof. Dr. Moestopo (Beragama), 2020)
The phenomenology of women with a career as a Flight Attendant was observed to overcome difficulties in communication with their husbands, which created a crisis in their marriage, which makes the researcher interested to raise this topic. The crisis in marriage starts from a misunderstanding in the communication. When the differences begin to arise is not done through excellent communication, often to be ignored so that it continues growth until separated. This study aims to look at the ten communication patterns of relational development model in a relationship when it begins, grows, survives and ends - starting from the five stages of coming together and followed by five stages of coming apart. The method used in this study is qualitative and supported by relational development model with some characteristics of interpersonal communication. The results of the study show that all flight attendants experienced all the elements in the stage of coming together with excellent communication and interaction.Two flight attendants reached the end element of coming apart, which is terminating (divorce). One flight attendant survived through marriage counseling, and one flight attendant stuck in the avoiding stage. The cause is from various factors.